The Intellectual Capital’s Effects on Banking Companies Financial Performance Before and During the Covid-19 Pandemic - Naufal Attallah Dirha Kirana; Atmini, Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aimed to examine intellectual capital's effect on company financial performance before and during covid19 pandemic. The independent variables used in this research are intellectual capital consisting of HCE (Human Capital Efficiency), SCE (Structural Capital Efficiency, and CEE (Capital Employed Efficiency). This study used secondary data in the form of an annual report collected through the Indonesia Stock Exchange (IDX). This research used a purposive sampling method. The sample of this study consisted of 47 banking companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. This study applied the multiple regression analysis method. The results showed that Human Capital Efficiency (HCE) and Structural Capital Efficiency (SCE) significantly affect firm financial performance. However, Capital Employed Efficiency (CEE) does not significantly affect firm financial performance. Abstrak Penelitian ini bertujuan untuk menguji pengaruh Intellectual Capital terhadap kinerja keuangan perusahaan pada masa sebelum dan selama pandemi covid19. Variabel independen yang digunakan dalam penelitian ini adalah intellectual capital yang terdiri dari komponen HCE (Human Capital Efficiency), SCE (Structural Capital Efficiency) dan CEE (Capital Employed Efficiency). Penelitian ini menggunakan data sekunder berupa laporan keuangan yang diperoleh melalui Bursa Efek Indonesia (BEI). Penelitian ini menggunakan metode purposive sampling. Sampel penelitian ini terdiri 47 perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) pada periode 2018-2021. Model analisis menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa Human Capital Efficiency (HCE) dan Structural Capital Efficiency (SCE) berpengaruh signifikan terhadap kinerja perusahaan. Namun, Capital Employed Efficiency (CEE) tidak berpengaruh secara signifikan terhadap kinerja keuangan perusahaan.